2022
DOI: 10.1111/1365-2664.14309
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing ecological surveys for conservation

Abstract: Conservation decisions must be made with limited funding and incomplete information. Ecological surveys can help reduce uncertainty and, in turn, potentially lead to better management decisions. However, conducting surveys can reduce funds available for implementing management actions and, in turn, can potentially lead to worse conservation outcomes. Here we develop a value of information framework to evaluate and optimize survey plans. Our framework evaluates survey plans based on their ability to improve how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Having such concepts available allows for predictions of high accuracy (see 132 for 1 m prediction resolution), specifically when it comes to impact assessments, e.g. with an optimized survey design 133 , done into the future and with climate change (e.g. 134 - 136 ).…”
Section: Discussionmentioning
confidence: 99%
“…Having such concepts available allows for predictions of high accuracy (see 132 for 1 m prediction resolution), specifically when it comes to impact assessments, e.g. with an optimized survey design 133 , done into the future and with climate change (e.g. 134 - 136 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify those basins that better complement the current network of protected areas in representing subterranean species, we computed the minimum set of basins that represent all the gap species at least once in our study areas. For this, we used the R package 'prioritizr' v.7.1.1 with Gurobi solver (Hanson et al, 2023), which uses mixed integer linear programming techniques to solve conservation planning problems. Because there were multiple optimal solutions, we computed conservation importance (irreplaceability) scores for each basin following Ferrier et al (2000) as implemented in 'prioritizr'.…”
Section: Effectiveness Assessment Of Protected Areasmentioning
confidence: 99%
“…In most cases, it is difficult to separate the effect of how complete biological datasets are from other confounding factors (Kujala et al, 2018). Increasingly, methods are being developed to test the effectiveness and improve the utility of additional data collection (Callaghan et al, 2019;Hanson et al, 2023;Mesaglio et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…limited money to spend, challenges in filling data gaps efficiently and adequacy of existing data), ongoing survey efforts yield limited value. Other studies have found either support for additional data collection (Chowdhury et al, 2023;Hanson et al, 2023;Ware et al, 2018) or mixed (Field & Elphick, 2019;Rodewald et al, 2019) or limited support (Maxwell et al, 2015;Mentges et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation